Strategi Dan Penerapan Enam Standar Pelayanan Minimal Posyandu di Provinsi Kepulauan Riau: Strategy and Implementation Six of Minimum Service Standards Posyandu in Riau Islands Province - Indri Ayu Ningsih; Dewi Kumalasari; Deri Noverlian (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
Strategy and implementation of six minimum service standards for Posyandu as an Integrated Service Post in the Riau Islands Province include education, health, public works, public housing, social, public order, and community protection. The aim is to determine the level of public satisfaction with the quality of Public Services. The Public Satisfaction Survey is a necessity for Regional Government Agencies that organize public services to improve the performance of Posyandu which is a reflection of public service performance and identify public expectations for Public services at Posyandu throughout the Riau Islands Province. This study is an observational study that is descriptive qualitative through observation using data on the SIDEWI Application. The results showed that there were 3.054 Respondents who filled out the Consumer Satisfaction Survey with an IKM of 86.92 Good Predicate for the six Community Service Standards at Posyandu throughout the Riau Islands Province.